Anomaly inflow and gauge group topology in the 10d Sugimoto string theory - Larotonda, Vittorio; Lin, Ling (The journal of high energy physics, 2025)
A bstract We revisit the chiral spectra on charged 1- and 5-branes in the 10d non-supersymmetric sp 16 string theory (also known as the Sugimoto model), and verify that they consistently cancel the anomaly inflow induced by a Green-Schwarz mechanism in the bulk. By analyzing the sp 16 representations arising from quantizing the fermion zero modes on these branes as well as uncharged 4-branes, we find compelling evidence that the global structure of the gauge group is Sp(16)/ ℤ 2 . We further comment on a possible duality to non-supersymmetric heterotic strings, and explore bottom-up anomaly inflow constraints for 10d effective Sp(16)/ ℤ 2 gauge theories coupled to gravity.